Impact of COVID‐19 Vaccination on Menstrual Irregularities, Bleeding Patterns, and Cycle Duration: A Systematic Review and Meta‐Analysis - Ganesh Bushi; Abhay M. Gaidhane; Nasir Vadia; Soumya V. Menon; Kattela Chennakesavulu; Rajashree Panigrahi; Muhammed Shabil; Diptismita Jena; Harish Kumar; Anju Rani; Sanjit Sah; Shivam Rohilla; et al. (Health Science Reports, 2025)
Abstract Background COVID‐19 vaccination has raised concerns regarding its potential effects on women's reproductive health, particularly menstrual irregularities. This systematic review and meta‐analysis aimed to assess the impact of COVID‐19 vaccination on menstrual disturbances, bleeding patterns, and cycle duration among women of reproductive age. Methods A systematic search of PubMed, Embase, and Web of Science was conducted up to April 11, 2025. The study protocol was registered with the PROSPERO (CRD42024500832). Studies reporting menstrual changes postvaccination in women aged 13–50 were included. Data extraction and quality assessment were performed independently by two reviewers. Meta‐analyses using random‐effects models were conducted in R (version 4.3), with heterogeneity assessed using the I² statistic. Results Out of 586 records, 43 studies comprising 747,763 women met the inclusion criteria. The pooled RR for menstrual disturbances in vaccinated versus unvaccinated women was 1.03 (95% CI: 0.67–1.57; p = 0.88), indicating no significant association. Excluding one outlier increased the RR to 1.14 (95% CI: 0.97–1.34; p = 0.08). The overall pooled prevalence of menstrual disturbances postvaccination was 34% (95% CI: 26%–43%). Among vaccinated women, lighter bleeding was reported in 12.6%, heavier bleeding in 15.1%, irregular menstruation in 19.0%, and regular cycles in 56.6%. Shortened cycles occurred in 8.5%, longer cycles in 9.3%, amenorrhea (≥ 24 days) in 9.2%, and infrequent cycles (> 38 days) in 11.0%. All analyses showed high heterogeneity (I² = 98%–100%). Sensitivity analyses confirmed the robustness of findings, though Egger's test indicated potential publication bias (p = 0.0384). Conclusion COVID‐19 vaccination was not significantly associated with an increased risk of menstrual disturbances. Although minor changes such as altered bleeding patterns and cycle length were observed in some women, the overall impact on menstrual health was minimal.